2017
DOI: 10.1097/md.0000000000006832
|View full text |Cite
|
Sign up to set email alerts
|

Association between common polymorphisms in ERCC gene and glioma risk

Abstract: Background:A number of studies have investigated the roles of excision repair cross complementation group 1 (ERCC1), ERCC2, and ERCC5 genes polymorphisms in the development of glioma; however, the results were inconsistent. Here, we performed a meta-analysis to investigate the association between 6 polymorphisms in the ERCC genes (rs3212986, rs11615, rs13181, rs1799793, rs238406, rs17655) and glioma risk.Methods:The PubMed, Embase, and Web of science were searched up to September 6, 2016, for studies on the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…Based on meta-analysis, the AC genotypes of ERCC2 rs13181 in Asians and Caucasians and the CC genotypes in Caucasians were associated to an increased risk of gliomas. This result corroborates the ndings reported by Qian et al [6], who reviewed fteen studies and conducted a meta-analysis [38]. These investigators reported increased risks for the development of glial cell tumors only in Asians with the CC and AC genotypes (Figs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Based on meta-analysis, the AC genotypes of ERCC2 rs13181 in Asians and Caucasians and the CC genotypes in Caucasians were associated to an increased risk of gliomas. This result corroborates the ndings reported by Qian et al [6], who reviewed fteen studies and conducted a meta-analysis [38]. These investigators reported increased risks for the development of glial cell tumors only in Asians with the CC and AC genotypes (Figs.…”
Section: Discussionsupporting
confidence: 91%
“…There are published reports on the relationship between some ERCC2 SNPs and the risk of systemic tumors with the most studied being ERCC2 Lys751Gln (rs13181). This polymorphism is characterized by the replacement of thymine (T) by guanine (G) at the locus 751, which changes the enzymatic activity of some encoded proteins, such as helicase, and can be associated with several types of cancers, including gastric, esophageal, hepatocellular carcinoma, non-small cell lung, prostate, skin, and bladder cancers, as well as gliomas [6]. Our current study reviewed and analyzed ten published reports that included ve based on Asian populations, four based on Caucasian populations, and one that included both populations and the genotypes studied in these reports were AC, CC, GG, and TG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…polymorphism was significantly associated with glioma risk under the following genetic models, and no association was observed between glioma risk and ERCC5 rs17655. 23 However, Hou et al found that rs6498486 polymorphism not associated with risk of colorectal cancer and rs3212986 may be associated with colorectal cancer risk in a Chinese population. 20 In addition, in recently published metaanalyses, Zeng et al 24 suggests that the ERCC5 rs17655 polymorphism might contribute to genetic susceptibility to colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the studies was modified from previous meta-analysis and independently assessed by 2 authors (Tables 1 and 2) [17,18]. Quality scores ranged from 0 points to 13 points and 0 points means the while 13 points means the best.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%